1995
DOI: 10.3109/10673229509017185
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-Onset Bipolar Disorder: A Neglected Clinical and Public Health Problem Gianni

Abstract: Bipolar disorder (BPD), probably the most prevalent psychotic disorder in adults, has been relatively neglected or controversial in children and adolescents over the past century. We reviewed the literature on early-onset BPD. Estimates of prevalence, particularly before puberty, are limited by historical biases against pediatric mood disorders and by formidable diagnostic complexity and comorbidity. Although clinical features of pediatric and adult BPD have similarities, pediatric cases probably cannot be def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
98
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 215 publications
3
98
0
3
Order By: Relevance
“…Retrospective assessments of patients with bipolar disorder found that for most individuals there is a large time gap between onset of the disorder and first-time diagnosis. 21,29 The more recent international debate in child and adolescent psychiatry on early symptoms of bipolar disorders might have also contributed to giving Danish clinicians a greater clinical awareness of the early manifestation of bipolar disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective assessments of patients with bipolar disorder found that for most individuals there is a large time gap between onset of the disorder and first-time diagnosis. 21,29 The more recent international debate in child and adolescent psychiatry on early symptoms of bipolar disorders might have also contributed to giving Danish clinicians a greater clinical awareness of the early manifestation of bipolar disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Second, and related to this debate, the extension of the psychopathological features of early onset bipolar disorders [18][19][20][21][22][23][24] might have also directed the awareness of clinicians to the lesser known characteristic features of bipolar disorders in young people, such as irritability or less pronounced mood swings. In addition, given the fact that the psychopathological phenomena of early-onset bipolar disorder are somewhat different from those of classical adult-onset bipolar disorder, there is more room for clinical interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed aver age pro phy laxis latency of 9.3 years (Table 1) may actu ally be even lon ger, since ill ness onset is often dated from first diag no sis rather than first symp tom atic presen ta tion, and the stud ies con sid ered here did not address effects of inter ven tion in the very first months of symp toms. More over, many cases of BD II are misdiagnosed and potentially mis treated as cases of recur rent non-BD major depression, and cases start ing in child hood or ado les cence may be dif fi cult to rec og nize as BD (34). An indi ca tion of this diagnos tic prob lem is that the mean onset age in the stud ies we reviewed was 31 years, whereas a review of early-onset BD sug gested a median onset age of about 20 years (35).…”
Section: Discussionmentioning
confidence: 99%
“…Such delays often are longer in women and in bipolar II disorder than in men and in bipolar I disorder / Baethge et al, 2003/. This delay underscores the need for much earlier diagnosis and treatment especially in juveniles, since delay of treatment may increase suicidal risk /Faedda et al, 1995/. Suicide rates in bipolar patients are also characterized by high lethality of suicide attempts: one death out of three attempts, compared to one completed suicide out of 30 attempts in the general population / Aubry et al, 2007/. Analyzing the clinical characteristics of 230 inpatients with recurrent major depression, Bulik et al /1990/ found that bipolar II diagnosis was significantly more frequent among the 67 patients who attempted suicide (19%) than in the 163 patients who did not attempt suicide (9%). Dunner et al /1976/ reported that 3% of the 73 unipolar, 6% of the 68 bipolar I and 18% of the 22 bipolar II patients died by suicide during their 1-9 year follow-up study.…”
mentioning
confidence: 99%